Benign paroxysmal positional vertigo commonly occurs following repair of superior canal dehiscence. (15th December 2015) - Barber, Samuel R.; Cheng, Yew Song; Owoc, Maryanna; Lin, Brian M.; Remenschneider, Aaron K.; Kozin, Elliott D.; Lee, Daniel J.
Abstract : Objectives/Hypothesis: Repair of superior canal dehiscence (SCD) often results in the resolution of preoperative auditory and vestibular symptoms; however, many patients experience dizziness in the postoperative period. Postoperative dizziness may be the result of new‐onset benign paroxysmal positional vertigo (BPPV). This study aims to investigate the prevalence of BPPV before and following SCD repair. Study Design: Retrospective chart review at a tertiary care center. Methods: Electronic medical records were reviewed for patients with a diagnosis of SCD syndrome (SCDS) between January 2002 and May 2015. Collected information included demographic data, incidence of BPPV diagnosed by Dix‐Hallpike maneuver before and following surgery, operative technique, repair material, and the duration of time to BPPV onset. Results: A total of 180 patients with a diagnosis of SCDS were identified: 84 patients underwent surgery (operated subjects) and 96 were observed (nonoperated, control group). In operated subjects, 20 of 84 (23.8%) developed BPPV following SCD repair versus 6.2% of nonoperated ( P < 0.005). Benign paroxysmal positional vertigo lateralized to the operated side in all but one subject whose laterality was unknown ( P < 0.0001). There were no associations of BPPV with surgical approach ( P = 0.50) or repair material ( P = 0.33). The majority of subjects (58%) were diagnosed with BPPV within 3 months of surgery. Conclusion: New‐onset BPPV occurs commonly after SCD repair and may be the result of mobilized otoliths from inner ear pressure changes. Although the exact etiology of post‐SCD repair BPPV remains unknown, postoperative dizziness is important to discuss with patients during preoperative counseling. Level of Evidence: 4. Laryngoscope, 126:2092–2097, 2016